Occurrence and Risk Factors for New Dependency on Chronic Care, Respiratory Support, Dialysis and Mortality in the First Year After Sepsis - Spoden, Melissa; Hartog, Christiane S.; Schlattmann, Peter; Freytag, Antje; Ostermann, Marlies; Wedekind, Lisa; Storch, Josephine; Reinhart, Konrad; Günster, Christian; Fleischmann-Struzek, Carolin (Frontiers in Medicine, 2022)
Sepsis survival is associated with adverse outcomes. Knowledge about risk factors for adverse outcomes is lacking. We performed a population-based cohort study of 116,507 survivors of hospital-treated sepsis identified in health claims data of a German health insurance provider. We determined the development and risk factors of long-term adverse events: new dependency on chronic care, chronic dialysis, long-term respiratory support, and 12-month mortality. At-risk patients were defined by absence of these conditions prior to sepsis. Risk factors were identified using simple and multivariable logistic regression analyses. In the first year post-sepsis, 48.9% (56,957) of survivors had one or more adverse outcomes, including new dependency on chronic care (31.9%), dialysis (2.8%) or respiratory support (1.6%), and death (30.7%). While pre-existing comorbidities adversely affected all studied outcomes (>4 comorbidities: OR 3.2 for chronic care, OR 4.9 for dialysis, OR 2.7 for MV, OR 4.7 for 12-month mortality), increased age increased the odds for chronic care dependency and 12-month mortality, but not for dialysis or respiratory support. Hospital-acquired and multi-resistant infections were associated with increased risk of chronic care dependency, dialysis, and 12-month mortality. Multi-resistant infections also increased the odds of respiratory support. Urinary or respiratory infections or organ dysfunction increased the odds of new dialysis or respiratory support, respectively. Central nervous system infection and organ dysfunction had the highest OR for chronic care dependency among all infections and organ dysfunctions. Our results imply that patient- and infection-related factors have a differential impact on adverse life changing outcomes after sepsis. There is an urgent need for targeted interventions to reduce the risk.